'Budd Chiari Syndrome' - A Case Report - Rahman, Md. Mukhlesur; Haque, KMHS Sirajul; Siddiqui, Md. Mahmudur Rahman; Parvin, Tanjima; Ahmed, Md. Khurshed (University Heart Journal, 2008)
'Budd Chiari syndrome (BCS)' is an uncommon condition induced by thrombotic or nonthrombotic obstruction to hepatic venous outflow. This disease can be potentially life-threatening but prognosis is more favorable in patient with IVC webs but is extremely poor in malignant and haematological cases. A cooperative collaboration of hepatologist and cardiologist can make the situation easy for diagnosis, even in treatment of some cases. (University Heart Journal 2007; 3 : 80-82)